Factors affecting performance of co-operatives in Malaysia. Issue 5 (13th June 2016) - Hammad Ahmad Khan, Hafizah; Yaacob, Mahazril 'Aini; Abdullah, Hussin; Abu Bakar Ah, Siti Hajar
Abstract : Purpose: – The purpose of this paper is to investigate the factors affecting co-operatives performance by focussing on the roles of its intangible assets which are in the form of intellectual capital and members' participation. Design/methodology/approach: – Questionnaires have been distributed among co-operatives board of members of the 100 best co-operatives in Malaysia. This study used Pearson correlation and multiple regression analysis to examine the impact of intellectual capital and members' participation on the co-operatives performance and determine the most influencing factors that affect the performance. Findings: – Results showed that there is a positive relationship between structural capital, relational capital and members' participation with the co-operatives performance while human capital has been found to have a negative relationship. This is further supported by the findings based on the multiple regression analysis whereby all the independent variables were found to be significant expect for structural capital. Based on the findings, this study proposed a model for co-operatives' performance which is based on its intangible assets. Practical implications: – Findings of this study would provide guidance for the co-operatives sector to improve its performance and indirectly help the government in realizing the nation economic goals. Originality/value: – This study provided a better understanding on the performance of the co-operatives by focussing on the roles of its intangible assets. Apparently, there are very limited studies on intellectual capital which is based on co-operative framework and thereby this present study would fill in the gap. In addition, due to the objective of the co-operatives which differs from other types of organization, findings of this study might provide significant contribution on the study of intellectual capital.